PENGARUH SERTIFIKASI GURU DAN MOTIVASI KERJA TERHADAP KINERJA GURU - Ristianey, Fenti; Harapan, Edi; Destiniar, Destiniar (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2021)
This research determined the relationship between teacher certification and work motivation to teacher performance. The population taken in this research are teachers who have been certified to the state Junior high School in Kertapati district of Palembang for 94 people and the sample is the entire population. Research conducted following quantitative descriptive research procedures. The methods used in this research are quantitative descriptive giving answers to the formulation of this research problem. Therefore, the main data used in this research form a number. Data collection techniques through questionnaires, observations, documentation and library studies. The results of the study showed (1) the teacher's certification and work motivation positively affect the teacher's performance, (2) The certification of teachers positively impact the teacher's performance, (3) The motivation of work positively influence the teacher's performance.